Constituting 'The Poor': A Critical Frame Analysis of Substantive Claims. Issue 2 (2nd July 2016) - Schouteden, Anke; Wauters, Bram
Abstract : Following recent trends in the literature, substantive representation does not only take place in parliament by elected actors, but in a wide range of arenas involving diverse actors. In this article we study substantive claims about 'the poor' in newspaper articles using Critical Frame Analysis. Our aim is twofold: exploring which actors represent the interests of poor people, and how 'the poor' as a group are giving meaning to. Our findings show that poor people depend largely on a broad range of non-elected actors, including actors usually not associated with interest representation, such as academics. As for defining the group at stake, about half of the claims framed 'the poor' as an abstract group, while the other half address a multiplicity of subgroups, with child poverty as most prominent one. Nevertheless, some subgroups (even those with a high risk on poverty) are not addressed at all.